Parental reproductive liberty for choosing the sex of their offspring - Haneef, Sayed Sikandar Shah (Medicine, law & society, 2019)
Technological developments in the domain of fertility treatment in spite of thier utilitarian uses come with a plethora of ethico-religious challenges for people of faith particularly if they contradict some of their core religious values and beliefs about human procreation. The most disruptive among such challenges is declaring parental choice of a specific gender to their future offspring as part of their reproductive liberty (right). As to how major semitic religions, such as Christianity and Islam respond to it, the answer is polemical. Christianity genrally objects to it mainly because it turns procreation into a manufacturing business instead of leaving the sex of a baby to God. The Islamic position, on the other hand, is less rigid as the majority of Sunni Muslim legists, without much reflections on its ethical dilemmas, approve it not only for medical reason but also family balancing while dissenting views among them consider it a direct affront on what God has declared to be His domain of perfection of human procreation. This paper, therefore, argues that defining parents` decision on sexing a "right" or "liberty" is difficult to maintain unless a far-fetched perspective of scriptural texts is adopted.
Keywords: christianity; fertility; islamsko pravo; krščanstvo; muslim law; reproductive liberty; sexing; zunajtelesna oploditev